Forensic DNA Phenotyping: Regulatory Issues - Koops, Bert-Jaap; Schellekens, Maurice (Science and Technology Law Review, 2008)
Forensic DNA phenotyping is an interesting new investigation method: crime-scene DNA is analyzed to compose a description of the unknown suspect, including external and behavioral features, geographic origin and perhaps surname. This method is allowed in some countries but prohibited in a few others. Most countries have not yet taken a stance on this. This article addresses the question to what extent this investigation method should be allowed. The relevant regulatory issues are analyzed: the right of people not to know what their DNA tells about propensities for diseases or other propensities, data protection and privacy, stigmatization and discrimination, and the “slippery slope” argument. These are serious issues indeed, but their importance should not be overestimated. Current literature and legislatures seem overcautious. Phenotyping should be allowed for externally perceptible traits, such as hair color, and for non-sensitive behavioral traits, like left- handedness or a propensity for smoking. It should not be allowed for many propensities for diseases and for sensitive other information like a propensity for homosexuality or aggressiveness. The middle category of somewhat but not too sensitive traits could be allowed, for example, for early apparent medical disorders, like albinism or teenage-onset alcoholism. Ethnic origin and surname phenotyping are also compatible with fundamental rights, provided measures are taken to contain the risk of discrimination. It is also worth considering informing the suspect only of the fact of forensic phenotyping, leaving it to the suspect himself to request the test results.